PREFERENSI NARRATIF RDR 2 ANTARA GAME PEMAIN BATAM DENGAN PENDEKATAN MULTI METODE - Zulkarnain; Rifki (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2022)
The research conducted by the author aims to find out what makes RDR2 video game players like the narrative of the game. In this study the authors used two approaches, namely qualitative and quantitative. The variables used are Empathy (X1), Usability (X2) and Satisfaction (Y) variables. In the qualitative method, 30 samples were taken and in the quantitative method, 385 samples were taken from people who met the criteria, namely those who had played the video game RDR 2. The author collected qualitative research method data by conducting interviews with respondents, while the quantitative method collection technique was by distributing questionnaires to respondents. . For qualitative data, the data from the interviews will be coded before being tested and analyzed. Qualitative data, the writer can conclude that the Empathy variable is influenced by the Usability and Satisfaction variable by 80%, while 20% is influenced by other variables which include variables not examined by the authors in this study. In quantitative data, the authors can conclude that the Empathy variable is influenced by the Usability and Satisfaction variables by 34%, while 66% is influenced by other variables which include variables not examined by the authors in this study.